Design and Implementation of a Hybrid UWB Pulse Generator for Automotive Radar - Kim, Sang-Dong; Lee, Jonghun (Elektronika ir Elektrotechnika, 2014)
The design of a hybrid pulse generator that supports a variable pulse width and a pulse repetition interval (PRI) is proposed and demonstrated for an ultra-wide band (UWB) pulse-Doppler radar. UWB pulse-Doppler radar is required for implementing full digital systems for reliability and flexibility regardless of temperature. It is difficult to apply existing analog components and digital pulse generators with broadened pulse widths. To overcome these limitations, the pulse generator is developed using a digital pulse generator and a 24 GHz RF transmitter. The digital pulse generator is composed of a narrow bandwidth (NB) pulse generator and a pulse chopper based on a serializer-deserializer (SerDes) block on a field-programmable gate array (FPGA). The 24 GHz RF transmitter adopts a homodyne architecture. The digital pulse generator required 1 % of the FPGA Slice registers and 1 % of the FPGA Slice LUTs on a Xilinx Virtex-5 lx50. Using a 2 ns pulse width resolution and an 8 ns PRI resolution, we were able to change the pulse width and the PRI. The pulse width can be measured over the duration of 2 ns to 10 ns. DOI: http://dx.doi.org/10.5755/j01.eee.20.3.2774